Combined effects of basalt fiber geometrical characteristics on pavement performance of asphalt mixtures - Heng Zhou; Mengxin Li; Guyue Jin; Mengyu Guo; Yingjun Jiang (PLoS ONE, 2025)
Fibers have been widely adopted in asphalt mixture to improve its pavement performance. Lignin fiber and polyester fiber are the most popular two choices. Lignin fiber is derived from wood, which is not aligned with the principles of sustainable development. The production process for polyester fiber is more complex and costly, presenting both environmental and economic challenges in engineering applications. In contrast, basalt fiber is cost-effective, exhibit excellent wear resistance and impact toughness, and possess high mechanical strength. It is an ideal choice to improve pavement performance of asphalt mixtures. However, most of the existing studies focused on analyzing a single characteristic index of basalt fiber. They neglected the composite effects of geometric characteristics of basalt fiber, such as fiber diameter and length, on the pavement performance of asphalt mixtures at varying fiber contents. Therefore, taking the SMA-13 as an example, the combined effect of basalt fiber geometrical characteristics (fiber diameter, fiber length, and fiber content) on pavement performance are elucidated. Additionally, a random forest algorithm is adopted to perform a weight analysis of fiber characteristics and their correlation with pavement performance.